Existing Risks of Forest Fires in Radiation Contaminated Areas: A Critical Review - Yeremenko, Sergiy; Sydorenko, Volodymyr; Andrii, Pruskyi; Shevchenko, Roman; Vlasenko, Yevhen (Ecological Questions, 2021)
The purpose to highlight and focus on the most important risks of forest fires in radiationcontaminated areas, with some detailing of the problem in the Chernobyl Exclusion Zone (CEZ). The search strategy was to collect a sufficient number of relevant publications in ScienceDirect, PubMed, Mendeley, ResearchGate, GoogleScholar from 2006 to the present in English, Russian, Ukrainian. Requests were made on the topics "Forest fires in a radioactively contaminated area" and "Assessing the territories' radiation safety", as well as for the keywords of this study. Analysis of available open information about the CEZ was done. Although, in the future, temperatures are expected to rise in contaminated forests, and the amount of precipitation will remain the same or slightly decrease, which will contribute to an increase in the frequency of fires. Considering the socio-economic situation in Ukraine, the introduction of early detection systems is more profitable than the elimination of the consequences of such emergencies. Investigations have been studied, which were published after 2006 only in English, Russian, and Ukrainian. The most attention is paid to Chernobyl Exclusion Zone. Despite the fact that a lot of studies are devoted to the study of the ecological situation in radioactively contaminated areas, many issues related to safety still concern the population living in this area. The reason for this is intermittent fires, which again and again cover large areas with smoke and cannot be extinguished for a long time. To eliminate anxiety, it is necessary to convey truthful information to the population in the most accessible and convincing way. It was a critical look at numerous studies in this area that made it possible to present concentrated information understandable for most segments of the population. The document concentrates on the most key problems of fires in radioactive forests, shows the intensity of the radionuclides impact on the population and the exposure ways, as well as the probable risks. Such information is necessary to reduce the psychological stress that can be caused by the media influence. Objectively understood situation promotes constructive action in extreme conditions and reduces the likelihood of panic.